Measuring the Impact of Policies and Some Environmental Constraints on the Agricultural Sector in Iraq for the Period (1990-2024): (Wheat Crop as a Case Study) - Mohammed, Mohammed Thamer; Jasim, Omer Adel (International Journal of Aquatic Research and Environmental Studies, 2026)
This study aims to measure the impact of policies and some environmental constraints on wheat production in Iraq during the period (1990-2024) The study focuses on the role of Agricultural policies, including environmental policies, in addressing the environmental and climatic challenges that hinder the growth of the Agricultural sector, particularly wheat production in Iraq. The study relies on annual data issued by the Ministries of Agriculture, Planning, Trade, and Water Resources, as well as the Food and Agriculture Organization of the United Nations (FAO). The FAO Analyzed the data using Eviews 12 software and the Fully Modified Least Squares (FMOLS) methodology. The results showed an explanatory power with a coefficient of determination ( =0.886). They revealed a negative impact of certain environmental constraints. Specifically, a 1.5°C increase in temperature and a 30% decrease in rainfall during the period 1990-2024 exacerbated desertification’s, environmental degradation, and a decline in cultivated areas and productivity Regarding pricing policy, a direct relationship was found between domestic prices and agricultural production; a one-unit increase in price led to a 1.68-unit increase in production. The use of modern technologies contributed to the growth of the agricultural sector and the achievement of sustainable development. The study recommends adopting policies aimed at addressing environmental pollution and utilizing modern technologies to enhance food security.